Encapsulation of Bolbophorus damnificus (Digenea: Bolbophoridae) Metacercariae in Juvenile Channel Catfish, Ictalurus punctatus, Is Linked to Delayed‐onset Mortality. Issue 3 (19th October 2017) - Griffin, Matt J.; Khoo, Lester H.; Reichley, Stephen R.; Ware, Cynthia; Rosser, Thomas G.; Alberson, Neely R.; Woodyard, Ethan T.; Pote, Linda M.; Greenway, Terrence E.; Tiwari, Ambika; Mischke, Charles C.; Wise, David J.
Abstract: Bolbophorus damnificus (Digenea: Bolbophoridae) causes significant economic losses in catfish aquaculture in the southeastern USA. To determine mortality trends associated with B. damnificus exposure, three separate disease challenges were conducted. The first challenge exposed channel catfish, Ictalurus punctatus, fingerlings (7–13 cm) to approximately 285 B. damnificus cercariae/L, while the second exposed fish to approximately 215 cercaria/L. Fish were monitored for morbidity and mortality for 28 d. In both studies, mortality first occurred 8 d postchallenge (PC) and peaked at 9 and 10 d PC, respectively. Mortality had subsided by 14 d PC, with only sporadic mortality occurring >15 d PC. Dead and moribund fish presented with lesions consistent with B . damnificus infection. A third challenge was performed to record histological changes associated with parasite development from initial exposure up to the cessation of mortality. Catfish (2–5 cm) were exposed as described above to a range covering 0, 35, 70, 100, 150, 175, and 215 cercariae/L. Each day, two fish were sampled from each treatment. Mortality trends were consistent with previous challenges. The mortality window coincided with parasite encapsulation, neovascularization, and development of the host‐derived cyst, suggesting that morbidity and mortality are linked to host pathophysiological changes in response to metacercariae encapsulation.